The Strategies to Efficiency Promotion for Community Economy Management System Participatory Model in the New Normal of Lam Sai Community, Wang Noi District, Phra Nakhon Si Ayutthaya Province - Rangmeesrisuk, Jidapa; Krachaechan, Chanidapa; Kesanuch, Sompong; Kongprapun, Nuntaya; Gawnak, Naputr (Arts of Management Journal, 2023)
This article aimed to 1) synthesize a model of community economic management system of New Normal participatory model of the Lam Sai community and 2) present strategies for enhancing the community economic management system of New Normal participatory model of Lam Sai community. A mixed method research model was used, which combined the quantitative method of survey data from 400 samples with participant research. The research procedure was divided into 4 phases, namely: 1) the pre-treatment phase, which was a five communities discussion with a group of 12 people; 2) the research phase, which was a meeting with a group of 30 people as well as a focus group discussion with 12 people; 3) the conclusion phase, which was the presentation of the networking system with a focus group discussion of 12 people and a strategy presentation with a focus group discussion of 12 people; and 4) the follow-up phase, which was the organizing of a learning exchange forum for 50 people. The research tools were questionnaires, interview forms, and group discussions, and the used statistics were frequency, percentage, and mean. The result showed that the community economic management system model of the New Normal participatory model of the Lam Sai community has model code 53346. (5 management issues) (3 network sectors) (3 community capital systems) (4 management system dimensions) (6 management strategies) and system strengthening strategies for community economic management of the New Normal participatory model of Lam Sai community comprise 6 strategies, namely: (1) digital network development and management strategy; (2) community capital development and management strategy; (3) 360o participation strategy; (4) product and community service development strategy; (5) marketing strategy and management for product/community service/O2O; and (6) strategy for product sales management and community service system development.